Towards better communities manual and textual writing format on comprehensive shelter & land use plan formulation - Baguios, Erlinda G. (Legaspi City Housing and Urban Development Coordinating Council (HURDCC), 1993)
This manual is a guide for local government units, urban and regional planners and consultants. It provides guidelines and instructions on gathering the essential data required to present the socio-economic profile of a particular city and/or municipality and development need projections. It also provides instructions on the prototype textual writing format of plan elements and formulation of the zoning ordinance.
Contents: Guidelines and instructions on socio-economic profile of a particular city. Prototype textual writing format of plan elements. Formulation of zoning ordinance or municipal code.
Purpose: "To provide local government units with an ultimate guideline on how to prepare their comprehensive shelter and land use plan that responds to the growing demands of their communities."
Keywords: Land use -- Planning -- Handbooks, manuals, etc. -- Philippines; City planning -- Handbooks, manuals, etc; Housing -- Planning -- Handbooks, manuals, etc. -- Philippines